Electromagnetic Characteristics Measurement of Organic Material Absorber - Reza Septiawan; Sardjono Trihatmo; Juliati Junde; Dody A. Winarto; Arief Rufiyanto; Erik Madyo Putro; Budi Sulistya; Arky Astasari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Electro Magnetic Compatibility (EMC) Chamber requires high performance absorber material to assure the quality of EMC chamber related to Radio Frequency (RF) shielding effectiveness of the corresponding chamber. RF shielding effectiveness is measured following EN 50147-1 testing method. EMC laboratory of BPPT (Indonesian Agency for the Assessment and Application of Technology uses polyurethane absorber material which absorbs the carbon-neoprene mixture to maintain consistent RF performance over a broad frequency band, especially in the frequency range of CISPR 22 radiated emission test between 30 MHz to 6 GHz, limits in CISPR 22 (Information technology equipment-radio disturbance characteristics-limits and methods of measurement). This paper proposes alternative absorber materials based on organic materials: rice husk, coconut husk, cotton and sawn wood crumbs. In the early phase of this research, the frequency under consideration are 900 MHz and 1800 MHz. These frequencies are mostly used by mobile phone devices, therefore at this phase the resulted organic material absorber may be used for alternative mobile phone casing before to be used as absorber material for EMC laboratory in a broader frequency band. The organic materials are produced by mixing them with cement, carbon, and resin. Free space testing method is used in the measurements. Results has shown a mixture of 50% coconut husk with resin absorb the most radiated emission in 900 MHz, while 30% of coconut husk will absorb the most radiated emission in 1800 MHz.